2021
DOI: 10.3390/biomedicines9111679
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as a Major Factor and Therapeutic Target for Neuroinflammation in Parkinson’s Disease

Abstract: Mounting evidence suggests that ferroptosis is not just a consequence but also a fundamental contributor to the development and progression of Parkinson’s disease (PD). Ferroptosis is characterized as iron-dependent regulated cell death caused by excessive lipid peroxidation, leading to plasma membrane rupture, release of damage-associated molecular patterns, and neuroinflammation. Due to the crucial role of intracellular iron in mediating the production of reactive oxygen species and the formation of lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 129 publications
(146 reference statements)
0
25
0
Order By: Relevance
“…A characteristic of cell ferroptosis is the accumulation of lipid reactive oxygen species, leading to oxidative stress and cell death, which has been shown to have significant implications in diverse brain diseases [ 30 , 31 ], such as Alzheimer’s disease [ 32 ], Parkinson’s disease [ 33 ], and cerebral ischemic disease [ 34 ]. Ferroptosis process is closely related to oxidative stress, and usually accompanied by the increase of iron content.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic of cell ferroptosis is the accumulation of lipid reactive oxygen species, leading to oxidative stress and cell death, which has been shown to have significant implications in diverse brain diseases [ 30 , 31 ], such as Alzheimer’s disease [ 32 ], Parkinson’s disease [ 33 ], and cerebral ischemic disease [ 34 ]. Ferroptosis process is closely related to oxidative stress, and usually accompanied by the increase of iron content.…”
Section: Discussionmentioning
confidence: 99%
“…We found that silencing GDF15 impeded axonal regeneration and remyelination and aggravated nervous tissue loss post SCI. Previous studies have shown that overloaded iron-induced ferroptosis promoted the activation of microglia by a ROS-independent mechanism and the latter caused the secretion of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), which triggered neuroinflammation ( Ko et al, 2021 ). In our study, we observed that after deteriorative ferroptosis caused by the knockdown of GDF15, neuroinflammation post SCI was also more severe, which suggested that GDF15 was associated with ferroptosis-mediated neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Disease [85,86]. Ferroptosis is seen as a novel therapeutic for several neurodegenerative disorders including Alzheimer's, Parkinson's and Huntington's disease [87,88].…”
Section: Overview Of Ferroptosismentioning
confidence: 99%